Correlation Between Health Protocol With Covid-19 Cases In Workers In dr. Zainal Umar Sidiki Hospital - Rosmin Ilham (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The whole world is under the pressure of the COVID-19 outbreak, where the death toll rises, including the health workers. Action to prevent the increase in the outbreak can be applied by the health protocols. The study aims to analyze the correlation between the health protocols and COV1D-19 incident on workers at RSUD dr. Zainal Umar Sadiki. The study uses a cross-sectional study design. The populations are all medical workers durum COVID-19 while the application of total sampling as the sampling obtains 40 respondents. The result shows that 90% are good, and 87,5% of health workers are not confirmed with COVID-19, and 12,5% are confirmed with COVID-19. Based on the result of the test analysis using fisher exact test with j'-value: 0,004. The conclusion is that there is a correlation between health protocols sithCOVID-19 incidents on workers at dr. Zainal Umar Sadiki regional hospital. It is suggested to health workers to always comply with the health protocols in providing services to patients with COVID-19 suspected or to those who have been confirmed with COVID-19.